Hubungan Merokok dengan Penyakit Jantung Koroner di RSUD Prof. DR. W. Z. Johannes Kupang - Hattu, Diana A. M.; Weraman, Pius; Folamauk, Conrad L. H. (Faculty of Public Health, Nusa Cendana University, 2019)
A coronary heart disease is a disease which occurs because of the damage of blood vessel walls due to several factors of risk, such as free radical substances contained in cigarettes and pollution, cholesterol, hypertension, and smoking habits. The purpose of this study is to determine the correlation of smoking with coronary heart diseases. The research is an analytic survey with case control design. The population of this study were people who smoke that suffer from coronary heart diseases and those who do not suffer from the diseases. The sampling technique used in this study was simple random sampling, which consisted of 86 respondents. The respondents were divided into case and control sample respondents with similar number of people (43) respectively. The statistical test used was contingency coefficient test (c). The research shows that there was no correlation between jobs and family members health history towards the coronary heart diseases(p>0.05), whereas a correlation was found between the type of cigarettes, smoking intensity, sexes, duration of smoking, and the early age when smoking began with coronary heart diseases (p˂0.05).